Respostas termorreguladoras de cabras saanen e pardo alpina em ambiente tropical - Aiura, A. L. O.; Aiura, F. S.; Silva, R. G. [UNESP] (SciELO Espana/Repisalud, 2010)
Evaporation is the most effective way of thermolysis with high environmentmal heat load. This mechanism does not depend on the thermal gradient between the environment and animals. The aim of the present work was thermoregulatory responses, sweating rate (TS), rate frequency (FR) e rectal temperature (TR) of Saanen and Oberhasli goats under tropical environment conditions. The observed averages of responses were: TS= 142.91 ± 4.02 g.m-2h-1; FR= 73.23 ± 1.60 mov.min-1; TR= 39.28 ± 0.02oC.
Thermoregulatory responses of Saanen and Oberhasli goats in tropical environments
Keywords: Adaptation; Goats; Rectal temperature; Respiratory frequency; Sweating; Animalia; Capra hircus